(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The recently formulated entangled trajectory molecular dynamics (ETMD) theory is applied to the collinear hydrogen exchange reaction. The reaction probability is calculated for one- and two-dimensional of collinear H+H_2 model. It is found that although the results of ETMD are not in good agreement with quantum mechanics simulations, the numerical trend is consistent with each other.